2006
DOI: 10.1161/circulationaha.106.634709
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Administration of a Cell-Permeable Caveolin-1 Peptide Prevents the Development of Monocrotaline-Induced Pulmonary Hypertension and Right Ventricular Hypertrophy

Abstract: Background-Caveolins (Cavs), the principal structural proteins of caveolar microdomains, have been implicated in the development of pulmonary hypertension (PH). Mice with homozygous deletion of the Cav-1 gene develop PH and right ventricular hypertrophy (RVH). Reductions in pulmonary Cav-1 expression have been shown in several animal models of PH and in patients with severe PH. Whether in vivo modulation of Cav-1 expression could affect the development of PH and RVH remains unknown. Therefore, we investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
83
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(86 citation statements)
references
References 36 publications
3
83
0
Order By: Relevance
“…Close examination of individual cells in vivo showed that the specific endothelial cells that had a loss of cav-1 expression were the same cells with hyperactivation of PY-STAT3 and increased DNA synthesis (24). This reciprocal relationship between cav-1 downregulation and PY-STAT3 activation in PAH in the rat/MCT model was later confirmed by Jasmin and colleagues (19). That the increase in PY-STAT3 levels was seen before the onset of PAH in MCT-treated rats (19,24) and that the introduction of a cav-1 scaffolding domain peptide blocked PY-STAT3 hyperactivation and ameliorated indicated that STAT3 played a role in Address for reprint requests and other correspondence: P. B. Sehgal, Rm.…”
mentioning
confidence: 54%
See 2 more Smart Citations
“…Close examination of individual cells in vivo showed that the specific endothelial cells that had a loss of cav-1 expression were the same cells with hyperactivation of PY-STAT3 and increased DNA synthesis (24). This reciprocal relationship between cav-1 downregulation and PY-STAT3 activation in PAH in the rat/MCT model was later confirmed by Jasmin and colleagues (19). That the increase in PY-STAT3 levels was seen before the onset of PAH in MCT-treated rats (19,24) and that the introduction of a cav-1 scaffolding domain peptide blocked PY-STAT3 hyperactivation and ameliorated indicated that STAT3 played a role in Address for reprint requests and other correspondence: P. B. Sehgal, Rm.…”
mentioning
confidence: 54%
“…This reciprocal relationship between cav-1 downregulation and PY-STAT3 activation in PAH in the rat/MCT model was later confirmed by Jasmin and colleagues (19). That the increase in PY-STAT3 levels was seen before the onset of PAH in MCT-treated rats (19,24) and that the introduction of a cav-1 scaffolding domain peptide blocked PY-STAT3 hyperactivation and ameliorated MCT-induced PAH (19) indicated that STAT3 played a role in the initiation of PAH, at least in this animal model. Moreover, Park and colleagues (33) reported the hyperactivation of PY-STAT3 in lungs of cav-1 Ϫ/Ϫ mice, which spontaneously developed PAH.…”
mentioning
confidence: 54%
See 1 more Smart Citation
“…The downstream effects of PY-STAT3 are mediated by cyclin D1 (cell cycle regulator), survivin and B-cell lymphoma-extra large (Bcl-xL) (antiapoptotic factors), all reported to be upregulated in PH. Inhibition of STAT3 reduces the expression of cyclin D1, survivin, and Bcl-xL (36,60) and prevents neointima formation in the carotid artery injury model (116). Caveolin-1 acts as a suppressor of cytokine signaling and inhibits PY-STAT3 activation and modulates proinflammatory cytokines (61).…”
Section: Caveolae and Caveolin-1mentioning
confidence: 99%
“…In the MCT model, progressive loss of endothelial caveolin-1 and the activation of proliferative and antiapoptotic pathways occur before the onset of PH (48,78). The rescue of caveolin-1 inhibits the proliferative pathways (PY-STAT3, cyclin D1 and D3) and attenuates PH (47,60). Studies with caveolin-1 Ϫ/Ϫ mice have further underscored the importance of caveolin-1 in vascular health and disease.…”
Section: Disruption Of Ec Membranementioning
confidence: 99%